Association between physical activity and severity of diabetic retinopathy in patients with diabetes mellitus - Hassabi, Mohammad; Fakhri, Maryam; Salehi, Shahin; Abedi Yekta, Amir Hosein; Poursaeid Esfahani, Mehrshad; Malekifar, Parviz; Javadi, Fatemeh (Researcher Bulletin of Medical Sciences, 2021)
Background: Diabetes mellitus (DM) and its related complications such as diabetic retinopathy (DR) are among considerably growing global concerns. Many efforts have been done toward a better understanding of the modifiable risk factors of DR, to stop progression as well as prevention of this complication. Physical activity (PA) is a known modifiable risk factor of DM but its effect on the severity of DR is not clearly understood. In this study, we aimed to evaluate the association between PA and severity of DR. Materials and Methods: A case-control study was done comprising 232 patients with DM (type 1 or 2), 58 of whom were in control group with no sign of DR, while the others were divided into three subgroups each contained 58 individuals, according to the severity of DR. PA of patients was assessed by the International Physical Activity Questionnaire (IPAQ) short-version and total scores of PA were compared among different groups. Result: Total PA scores in (metabolic equivalent [MET]-hour/week) in control group, in patients with mild to moderate non-proliferative diabetic retinopathy (NPDR), severe to very severe NPDR, and proliferative diabetic retinopathy were 24.6 ±28.3, 23.7 ±30.6, 17.1 ± 27.0, and 7.1 ±10.2, respectively. The lower the score of PA, the higher the stage of DR (r=-0.284, p<0.001). Low PA levels came with higher stages of DR (odds ratio [OR]=2.7, P=0.023) than moderate PA (OR=2.1, P=0.114). When adjusted for age, sex, duration of DM, and type of medication regimen, the association of DR severity with PA level was still statistically significant in mild PA group (P=0.049) and statistically insignificant in moderate PA group (P=0.132). Adjusting for hemoglobin A1c (HbA1c) and body mass index (BMI) showed no significant correlation between PA level and DR severity (OR=1.1 and P=0.794 in low PA group, OR=1.2 and P=0.670 in moderate PA group). Conclusion: Low PA level can be identified as a risk factor for DR, but not a completely independent one. It is more likely that PA lowers the risk of DR progression through lowering BMI and achieving better glycemic control (HbA1c).